KEBIJAKAN HUKUM PIDANA DALAM PENANGGULANGAN TINDAK PIDANA KORUPSI YANG DILAKUKAN OLEH PEJABAT DAERAH - Mochamad Yuliandra Ekaloga, Eko Soponyono, Pujiyono (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Based on the facts and realities of the case, corruption in Indonesia appear to thrive, corruption mostly done by an officer / officials in the area. Criminal Law Policy can be defined as the general principles that serve to illustrate the government (in the broad sense, including law enforcement agencies) to manage, regulate or adjust public affairs, community issues or areas of drafting legislation and allocating legal / regulation with a purpose (general) directed to the welfare or prosperity of the people (citizens). In this regard, How the Criminal Law Policy Control of Corruption conducted by the Regional Officer Present and to Come?